Comparative Analysis of Board of Directors Term Limits Compliance in Public And Private Institutions (Case Study in Gambia) - Gissay, Amadou; Bah, Momodou Habib; Mamburay, Yankuba; Haule, Daigo Bernadetha (Universitas Bojonegoro, 2024)
This paper examines the comparative analysis of the board of directors’ term limits compliance in Non-Governmental Organizations and Public and Private Institutions in the Gambia. The objective of this study is to analyse the term limits of the board of directors in these three institutions and their impact on institutional performance. The study was conducted based on a sample size of 34 boards of directors using descriptive and thematic analysis approaches to analyze the data. The study found that institutions that comply with board tenure (term limits) enjoy rapid innovation and institutional growth compared to the institutions that neglect it. In addition, (Kroll et al., 2008) alluded that long-tenured directors are on the boards of scandal-ridden companies like Xerox, Worldcom, Tyco, and Enron and this lends credence to this viewpoint. Our findings also indicate that these companies have lower research and development (R&D), productivity and exploration intensity than their matched control companies. Further findings observed that board members have a term limit of 2.24 years on average. However, there is a considerable degree of fluctuation (standard deviation of 1.30). This shows that different institutions have different governance rules, with some having shorter-term restrictions and others allowing for longer periods. The study also recommends future research that may explore similar topics in diverse contexts, evaluating cultural differences in board dynamics and conducting assessments of governance protocols. You need to stick with either American or British English. E.g. be consistent with words like analyse or analyze. I have highlighted these two spellings because they’ve been used so many times and interchangeably. Please note the same for words like organisation and organization.